BLENDED LEARNING MEDIATED INSTRUCTION IN ENGLISH CLASS: STUDENT ENGAGEMENT - Farikah; Mimi Mulyani; Astuty; Aulya Cahyaningrum (Bajang Institute, 2022)
There have been many discussions on the concepts of student engagement in learning during Blended learning mediated instruction. Student engagement tended to be discussed in academic activities during Pandemic learning. This study explored the students’ engagement in a project-based blended learning classroom. It investigated how the project-based blended learning model motivates student engagement. A case study approach was adopted that involved ten English department students. Questionnaires and interviews were used to collect the data. Deci and Ryan’s theory (1985) opted to analyze the data. The results contribute to higher education pedagogy by providing insights into the use of project-based blended learning models in engaging students.